Determining the disturbed behaviors in a sample of Iraqi school students in Baghdad Governorate. - عجيل, م.م حامد زايرر عجيل (Journal of College of Education, 2023)
Disturbed behaviors and emotions received changes children.Determining the disturbed behaviors of a sample of Iraqi school students in Baghdad GovernorateThe school is the home of the second student, and it is the favorite place for children because they receive knowledge there, discover new things, meet friends, play, spend quality time, and participate in sports and artistic activities, etc. It is carried out by the school, so the research searched for the disturbed behaviors among a sample of school students in the Baghdad governorate. The research tried first to define the disturbed behaviors, then determined the method by which these behaviors are monitored, then made an inquiry and determined these behaviors and the extent of their prevalence among the selected sample. The extent of the seriousness of these behaviors And the way to address and deal with it in light of the available and possible tools.The danger of the student's disturbed behavior is that it may affect his classmates negatively, whether by imitating this behavior or being directly affected by it through exposure to physical or psychological harm because of this behavior. Therefore, identifying this behavior and dealing with it is important to purify the atmosphere in the school, which It is a place for learning and skills development for students.The research has tried to find the appropriate ground for the treatment of behavioral disorder through the recommendations that it put at the end of this research, as it is important that this disordered behavior be treated as a pathological behavioral condition that must be dealt with positively and openly.